Small towns and their surroundings in the context of local government reorganisation. Results from Schleswig-Holstein (Germany) - Axel Priebs (Rozwój Regionalny i Polityka Regionalna)
The importance of small towns for stabilising and supporting the development of rural regions is being gradually recognised in spatial research and planning. This paper discusses the status of small towns in local administrative reform processes. It is based on the example of reform processes that were carried out in the German state of Schle- swig-Holstein. At the end of this process, the small towns found themselves in very dif- ferent political and administrative constellations with respect to neighbouring districts. Strengthening towns as central service locations was not part of the state’s plans for reform. In several cases, even if a town had an efficient administration, the surrounding municipalities were not prepared to entrust their administration to the town, but rather perpetuated duplicate structures in a local “collar” district administration around the town. Steps for better efficiency and specialisation of employees were not implemented. It became clear that many small municipalities did not want to be administered by towns. As a final result, the concerns of the small towns were not taken into account sufficiently in the reform processes in question.